2000
DOI: 10.1159/000022932
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CCR5 and CCR2 HIV-Coreceptor Gene Polymorphisms in Belgium

Abstract: Polymorphisms of the chemokine receptor genes CCR5 and CCR2 are associated with resistance to HIV-1 infection or delayed progression to AIDS. Few data are available on their combined prevalence in healthy subjects; we therefore examined the occurrence of CCR5-Δ32 and CCR2-64I polymorphisms in a sample of 310 healthy Belgians. Allele frequencies were 0.119 and 0.074 for CCR5-Δ32 and CCR2–64I, respectively. Genotype distributions for both polymorphisms were found to be in accordance with Hardy-Weinberg equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…The CCR2 190A (64I) variant occurred with a frequency of 18%, which is comparable to what has been reported among other African populations (ranging from 10%-30%) [4,17]. These frequencies of the CCR2 190A allele in African populations are higher than what has been observed in Caucasians (7%-10%) [17,18], while Asian populations show a wider range (1%-30%) [15,19]. The distribution of the CCR2 190A allele among Caucasians, Africans, and Asians does not seem to exhibit trends suggestive of the variant's role in HIV restriction at the population level.…”
Section: Chemokine Receptor Polymorphism and Their Association With Hsupporting
confidence: 72%
“…The CCR2 190A (64I) variant occurred with a frequency of 18%, which is comparable to what has been reported among other African populations (ranging from 10%-30%) [4,17]. These frequencies of the CCR2 190A allele in African populations are higher than what has been observed in Caucasians (7%-10%) [17,18], while Asian populations show a wider range (1%-30%) [15,19]. The distribution of the CCR2 190A allele among Caucasians, Africans, and Asians does not seem to exhibit trends suggestive of the variant's role in HIV restriction at the population level.…”
Section: Chemokine Receptor Polymorphism and Their Association With Hsupporting
confidence: 72%
“…12,13 Higher frequencies have been reported for American blacks of African origin and Hispanics (0.15) and for Asians (0.25). 12,14 Additional studies will be required to determine whether the association with CAC reported in the present study is found in these populations as well.…”
Section: Discussionmentioning
confidence: 96%
“…The allele frequency of this polymorphism has been described to be between 0.1 and 0.25, depending on the ethnic background. 12,13 The Ile64 variant has been found to be associated with a lower risk of AIDS, 12 of pulmonary sarcoidosis, 14 and of acute renal transplant rejection. 15 These reports suggest that the Ile64 allele may be associated with reduced CCR2 function.…”
mentioning
confidence: 99%
“…It has been shown that its distribution is strongly dependent on ethnicity 45,46,47,48 . Its mutation leads to the substitution of valine by isoleucine (V64I) in the transmembrane region of the protein.…”
Section: Ccr2v64i Polymorphism and Its Functional Consequencementioning
confidence: 99%